The railway Minister, Prince M.I. Khilkov (1834–1909): the life and work activities - O. Ya. Pylypchuk; O. H. Strelko (History of science and technology, 2016)
The article highlights the life and work activities of an outstanding Railway minister (1895–1905), the man of amazing destiny, prince, a direct descendant of the Rurik princes, Mykhailo Ivanovych Khilkov. His life experience from the locomotive boiler fireman to the railway minister has been considered. It is shown that he had devoted all his life to serving Motherland.